Mitochondrial Genomes of Hibiscus Reveal Structural Heterogeneity and Phylogenetic Relationships - Jing Ge; Cheng-Ao Yang; Jia-Yi Wu; Jia-Yu Xue (Horticulturae)
Hibiscus, which belongs to the Malvaceae family, is primarily distributed in tropical and subtropical regions. Hibiscus species are known for their large, visually striking flowers, which are highly valued for ornamental purposes and are widely admired. Despite this diversity, the mitochondrial DNA of Hibiscus species remains largely unexplored. Here, we assembled chromosome-level mitochondrial genomes (mitogenomes) of H. schizopetalus, H. syriacus, H. hamabo, and Talipariti tiliaceum (Hibiscus tiliaceum) using Illumina short reads (Illumina, Inc., San Diego, CA, USA) and PacBio long reads (Pacific Biosciences of California, Inc., Menlo Park, CA, USA), and conducted comparative genomic analyses. Our findings revealed that the mitogenomes of Hibiscus species exhibited structural complexity, including variable sizes and multi-molecular configurations, while maintaining high conservation in codon usage bias and GC content. Repeat sequence analysis suggested that repeat-mediated homologous recombination played a critical role in frequent recombination events in the mitogenomes. In addition, phylogenetic analysis showed that Hibiscus species did not form a monophyletic clade, and H. hamabo and T. tiliaceum were positioned in sister clades, which was consistent with the results of synteny analysis. To sum up, our study provides valuable resources for phylogenetic research and makes significant contributions to exploring further genetic mechanisms and biodiversity of Hibiscus species.